Life cycle embodied carbon evaluation of a two-bedroom house construction in Ghana: A comparison between stabilized laterite and sancrete building - Theophilus Frimpong Adu; Mohammed D.H. Zebilila; Peter Adzakey; Wilson Ofori Sarkodie; Zakari Mustapha (Heliyon)
This study investigated the embodied carbon (EC) emissions of stabilized laterite brick and sancrete block buildings in the Ghanaian construction industry using a cradle-to-site life cycle assessment (LCA) approach. The findings reveal that the embodied carbon footprint of laterite brick is basically due to the cement content. An air-dried stabilized laterite brick (1:1.6:8.1 ratio of cement, sand and laterite) used in the study exhibited a higher EC of 0.0505 kgCO2e/kg compared to sancrete block (1:16 ratio of cement to sand) of 0.0336 kgCO2e/kg. However, despite the higher EC per kilogram of stabilized laterite brick bricks, the overall stabilized laterite building demonstrated a significantly lower EC per square meter (268.16 kgCO2e/m2) compared to sancrete buildings (313.39 kgCO2e/m2). This is because the stabilized laterite buildings required less plastering, reducing the amount of cement used and paint for finishing. The plastering and paint used in sancrete buildings contribute to higher embodied carbon emissions. This study highlights that replacing cement and paint with lower embodied carbon materials could be a promising strategy for sustainable construction. Further research is recommended to include the entire building life cycle, encompassing not only the construction phase but also the operational and end-of-life stages. Air-dried laterite bricks offer a practical and sustainable choice for Ghana's built environment due to their lower embodied carbon footprint and reliance on locally available materials.